Active school transport routines during school transitions: Socio-structural predictors of changes from childhood into early adulthood. (May 2023) - Klos, Leon; Burchartz, Alexander; Niessner, Claudia; Reimers, Anne Kerstin; Thron, Maximiliane; Woll, Alexander; Wäsche, Hagen
Abstract: The purpose of this study is to investigate socio-structural predictors of active school transport (AST) change and to explore the stability and changes of transport modes during school transitions and into early adulthood in Germany. School transport mode, urbanicity level, socioeconomic status, and migration background were assessed in 624 children (8.9 ± 1.1 years, 51% female) and 444 adolescents (14.9 ± 1.7 years, 48% female) which were followed up longitudinally six years later. The results of multinomial logistic regressions and transition probability calculations indicated that residing outside of rural areas at baseline and follow-up predicts retaining or switching to AST in adolescence. Similarly, higher socioeconomic status at baseline predicted retaining or switching to AST in early adulthood. This research suggests that transition periods are crucial understanding AST behavior and may provide new opportunities for tailored AST promotion programs for different age groups. Highlights: Active school transport rates decline after school transitions. Urban children are likely to maintain or switch to active transport in adolescence. Rural children mainly switch to public transport in secondary school. High socioeconomic status is associated with an active commute in early adulthood. Young adults predominately switch to car transport.